Educação para as relações étnico-raciais: concepções e práticas de professoras da educação infantil - Castro, Moacir Silva de (2015)
This work has as its object the conceptions and practices of teachers of the Childhood Education on ethnic and racial relations at school. The overall objective of the research intervention was to analyze which conceptions and practices guides in their teaching work with children of 4 and 5 years, with the prospect of an Education for ethnic and racial relations. There are specific objectives: To understand what theoretical and practical assumptions embody the conceptions and practices expressed by the teachers of Childhood Education regarding the ethnic and racial relations; To analyze if these conceptions and practices are being changed (or not) with the teachers participation in meetings of continuing training education on service; To identify theoretical-methodological principles to guide the training and the teaching practice of teachers of small children for an education of ethnic and racial relations, helping to combat the culture of prejudice and racial discrimination in the school environment. There were theoretical studies of authors such: Bento (2012), Cavalleiro (2003), Dias (2012), Freire (1996), Gomes (2000), Moore (2012), Moura (1988), Munanga (2003), Silvério (2003), among others. The research was conducted in a rural school, located in a city in the interior of the state of Sao Paulo, close to the metropolitan area, with three teachers who work in the education of children in the age between 4 and 5 years. This research was conducted under a qualitative perspective. The procedures for the reality collection of data were the following: Questionnaire with scripts of closed and open questions to draw the profile of the participant teachers and for an initial survey of their conceptions and practices in relation to the issues of ethnic and racial questions in Childhood Education; Accomplishment of eight meetings of continued education in service on the theme of ethnic and racial diversity in the school with a record in a field diary and audio recording; Classroom observation with field daybook and subsequent dialog with the teachers in the area of service training. As result it was observed that the conceptions of the teachers about ethnic and racial relations in Childhood Education were changing to the extent that the formation meetings proposed were held and the comments and the feedback were made pointing to the continued education of teachers on this theme represents a profitable journey to incorporate it in teachers reflections and practices.